Development and performance evaluation of solar heating system for biogas production process. (November 2022) - Gunjo, Dawit Gudeta; Yadav, Vinod Kumar; Sinha, Devendra Kumar; Elseesy, Ibrahim E.; Sayeed Ahmed, Gulam Mohammed; Abdelmohimen, Mostafa A.H.
Abstract: The breakdown of organic waste, through anaerobic digestion, is a temperature dependent process. Attaining the temperature required for this process, under normal conditions, is a challenging task. Hence, the development of an effective heating system is necessary. In this paper, a solar heater's computational fluid dynamics (CFD) model, with water as working fluid, is prepared to estimate the temperatures of the absorber plate and that of the water available at the outlet. The validations of the numerical results were done by conducting experimental trials and a fair agreement between them was observed. For the examined solar collector, with outlet temperature of 61°C, the maximum thermal efficiency was estimated as 71%. The effects of operating parameters (like transmissivity coefficient, ambient temperature, wind speed, inlet water temperature and sun's insolation), were explored. It was predicted that 30–60°C tank water temperature can be attained at flow rates of 0.00833, 0.0167, and 0.021 kg/s. The bent-tube Flat Plate Colector (FPC) model, proposed in the present work, increases the residence time of water in the collector. It also increases the outlet temperature. Hence, the developed FPC model may be considered as an alternative solution for growing thermophilic bacteria during the anaerobic digestion in biogas production.